Learning Motivation During COVID-19 Pandemic and the Academic Performance Among Agriculture Students of a State College - Morados, Alexander N. (Future Science / FSH-PH Publications, 2023)
Learning motivation has been known to be a basic determinant of academic achievement, and this can be negatively affected by a disease outbreak and a shift in teaching approach. This study aimed to determine the significant relationships among perception of learning motivation during the COVID-19 pandemic, learning motivation level, and academic performance of Bachelor of Science in Agriculture students of Camiguin Polytechnic State College. It used the explanatory-correlational design with a modified adapted questionnaire as the main data gathering instrument. The data were analyzed using descriptive statistics and Pearson correlation tool in the context of the theories of social learning, protection motivation, operant conditioning, goal-setting, and achievement motivation. Results revealed that respondents perceived their learning motivation during the COVID-19 pandemic as highly enhanced, just as they assessed their learning motivation level as high, although their intrinsic motivation was slightly higher than their extrinsic motivation. The correlation test yielded a significant positive relationship between the respondents' perception of their learning motivation during the pandemic and their intrinsic motivation. However, their learning motivation level had not proven significantly related to their academic performance, and neither had their learning motivation during the pandemic.